1984
DOI: 10.1128/iai.43.1.302-307.1984
|View full text |Cite
|
Sign up to set email alerts
|

I-E/I-C region-associated induction of murine gamma interferon by a haplotype-restricted polyclonal T-cell mitogen derived from Mycoplasma arthritidis

Abstract: Cell-free supernatants from cultures of Mycoplasma arthritidis induced significant levels of interferon when cocultured with murine splenic cells. On the basis of physicochemical characteristics and antibody neutralization studies, the antiviral substance was identified as gamma interferon. Use of inbred and congenic mouse strains established that splenic cells from mice expressing the H2k and H2d haplotypes produced interferon in response to M. arthritidis culture supernatants, but those from mice with H2b an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Mice possessing the H-2k or H-2d haplotype were susceptible, whereas those expressing H-2b appeared to be more resistant (10). Further influences asserted by the MHC haplotype were on an ulcerative dermal coagulation necrosis upon subcutaneous injection of M. arthritidis (7) and a reactivity of mouse lymphocytes toward M. arthritidis supernatants (MAS) acting as a soluble T-cell mitogen (5,9). Spleen cells from several inbred rat strains also showed a differential response towards MAS, but this was not associated with the rat MHC, RTJ (6).…”
mentioning
confidence: 99%
“…Mice possessing the H-2k or H-2d haplotype were susceptible, whereas those expressing H-2b appeared to be more resistant (10). Further influences asserted by the MHC haplotype were on an ulcerative dermal coagulation necrosis upon subcutaneous injection of M. arthritidis (7) and a reactivity of mouse lymphocytes toward M. arthritidis supernatants (MAS) acting as a soluble T-cell mitogen (5,9). Spleen cells from several inbred rat strains also showed a differential response towards MAS, but this was not associated with the rat MHC, RTJ (6).…”
mentioning
confidence: 99%
“…tested (Table III). The interferons induced by the three mitogens were acid-labile, and we assume them to represent IFN-y, since in mouse spleen cells the same mitogen induced IFN-y [5]. Definitive proof, however, is lacking in our rat experiments, since antisera to rat IFN-y were not available.…”
Section: Resultsmentioning
confidence: 91%
“…MAS, besides inducing a lymphoproliferative response, recently has also been found to induce IFN-y in mouse spleen cell cultures [5], and we were interested in testing whether this was also true of rat spleen cells. MAS was indeed as potent as PHA or Con A in inducing IFN.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be relevant in the context of immunopathology. Recent experiments have indicated that MAS is also capable of inducing gamma interferon production by T lymphocytes [7], a phenomenon that is being investigated further in our laboratory.…”
Section: Discussionmentioning
confidence: 91%